SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS PADA KEC. BUARAN PEKALONGAN MENGGUNAKAN METODE AKRUAL BASIS - Teguh Setiadi; Nur Hidayah (Universitas Sains dan Teknologi Komputer, 2019)
Comput At this time in Buaran Subdistrict, Pekalongan District, there are many obstacles, one of which is the recording of cash receipts and disbursements which are very piling up because moreover in the implementation, it is still for manual recording, one of which is by means of counting, still using handwriting. Cash book, if you want to print financial statements and still use a lot of Microsoft Excel as data storage and printing a report, it takes too long for information system data to be a lot of completion data is not timely and makes it less efficient. With this information system, it is expected that all recording processes will be easier by using the Base Accrual Method, reports can also be printed accurately dated or per period. This information system is also more secure because it is equipped with a security system where not everyone can access it, and only people who have a login can access the data. The system built will later contribute to the District faster in work.